Place-Making of Transit Towns in Qatar: The Case of Qatar National Museum-Souq Waqif Corridor - Khalida Marthya (16441942) (2021)
Over the last two decades, Doha, the capital city of Qatar, has undergone rapid urbanization. The city has capitalized large-scale urban and infrastructural projects resulting in a loss of historical areas of heritage value to people. Recent construction of the Doha Metro is opening avenues for place-making of transit towns through a framework envisioned by the need to shape compact, livable and sustainable neighborhoods and to mitigate the effects of urbanization on valuable historical heritage sites. Due to its historic significance, the Qatar National Museum (QNM)-Souq Waqif corridor is the case study selected for exploring and defining a framework for a contextualized place-making transit-oriented development (TOD) model. The research design is structured by reviewing the literature about TODs and the need for place-making model in Qatar, followed by collecting visual data from municipal authorities, through site visits, and site observations. The data are then analyzed to propose a novel masterplan, rooted in key urban design components of place-making. The insights will contribute to proposals for context-driven design strategies to enhance livability of the site and to extend its application to other potential transit hubs in metropolitan Doha and in the Middle East. Other Information Published in: Designs License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.3390/designs5010018